Dragonbreath: No Such Thing as Ghosts #5 - Vernon, Ursula (New York : Dial Books, 2011)
Not only must Danny and Wendell trick-or-treat with skeptical classmate Christiana, school bully Big Eddy dares them to enter a haunted house on Halloween night, where they may have to sacrifice their candy to a ghost.
Keywords: Halloween -- Juvenile fiction; Haunted houses -- Juvenile fiction; Ghosts -- Juvenile fiction; Bullying -- Juvenile fiction; Dragons -- Juvenile fiction; Iguanas -- Juvenile fiction; Halloween -- Fiction; Haunted houses -- Fiction; Ghosts -- Fiction; Bullies -- Fiction; Dragons -- Fiction; Iguanas -- Fiction; Humorous Stories